Comprehensive School Health and Comprehensive Guidance and Counselling Programs: A Call for Collaboration - Gordon, Tamara R. (Canadian Journal of Counselling and Psychotherapy, 2007)
Four hundred and seven grade 10, 11 and 12 students, 170 parents, and 25 school personnel were surveyed regarding the health and guidance related needs of adolescents. The results were analyzed and compared within both the Comprehensive School Health (CSH) and Comprehensive Guidance and Counselling (CGC) frameworks. Within the CSH framework student self-reported priority needs related to school building and grounds, safety and accident prevention, and academic skills. Within the CGC framework student self-reported priority needs related to career information and planning, academic skills, and relationships with school staff. Significant differences were noted between students and both adult groups. The results suggest a need for collaboration between CSH and CGC program developers as well as between students, parents, and school personnel.